1991
DOI: 10.1039/dt9910000467
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the bonding in iron(II) cyclopentadienyl and arene sandwich compounds. Part 2. Correlations and interpretations of carbon-13 and iron-57 nuclear magnetic resonance and iron-57 mössbauer data

Abstract: Carbon-I 3 NMR data for [Fe(q-C,H,)(q-C,H,X)] and [Fe(q-C,H,)(q-C,H,X)]+ and 57Fe NMR data for neutral substituted ferrocenes, ferrocenyl carbenium ions and ferrocenophanes have been analysed and correlations between these data sets and those of the 57Fe Mossbauer quadrupole splitting (q.s.) are discussed on the basis of concepts put forward previously. For substituted neutral ferrocenes there is a linear relationship between q.s. and chemical shift 6(57Fe). For ferrocenyl carbenium ions the relationship sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
0
12
2
Order By: Relevance
“…For this reason, we have previously used indirect methods that rely upon ∼16.3 MHz decoupling of the ∼202.5 MHz 31 P doublet ( J = 36−59 Hz) that results from scalar coupling of 57 Fe to 31 P for a series of Fe(II) porphyrinate complexes having at least one trimethylphosphine (PMe 3 ) axial ligand. , However, since phosphines are not naturally-occurring ligands for heme proteins, we sought other means of predicting the approximate 57 Fe chemical shifts of diamagnetic iron(II) porphyrinates of biological importance and, hence, simplifying the search for the signals. Silver and co-workers previously reported an apparent correlation between the Mössbauer quadrupole splittings, Δ E Q , and the iron-57 chemical shifts, δ Fe , of a series of ferrocenes and related Fe(II) arene complexes, and we reasoned that a similar correlation might be observed for Fe(II) porphyrinates. Since Mössbauer spectra have frequently been reported for low-spin Fe(II) model hemes and heme proteins, values of Δ E Q are already available for some of the systems for which 57 Fe chemical shifts are known. In order to expand the body of available Mössbauer spectroscopic data to include the complexes having at least one trimethylphosphine ligand, , we have prepared a series of 94.5%-enriched 57 Fe(II) complexes of tetramesitylporphyrin (TMP) and octaethylporphyrin (OEP) having various bis- or mixed axial ligation, have used them for NMR studies, , and have now investigated them by Mössbauer spectroscopy.…”
Section: Introductionmentioning
confidence: 53%
“…For this reason, we have previously used indirect methods that rely upon ∼16.3 MHz decoupling of the ∼202.5 MHz 31 P doublet ( J = 36−59 Hz) that results from scalar coupling of 57 Fe to 31 P for a series of Fe(II) porphyrinate complexes having at least one trimethylphosphine (PMe 3 ) axial ligand. , However, since phosphines are not naturally-occurring ligands for heme proteins, we sought other means of predicting the approximate 57 Fe chemical shifts of diamagnetic iron(II) porphyrinates of biological importance and, hence, simplifying the search for the signals. Silver and co-workers previously reported an apparent correlation between the Mössbauer quadrupole splittings, Δ E Q , and the iron-57 chemical shifts, δ Fe , of a series of ferrocenes and related Fe(II) arene complexes, and we reasoned that a similar correlation might be observed for Fe(II) porphyrinates. Since Mössbauer spectra have frequently been reported for low-spin Fe(II) model hemes and heme proteins, values of Δ E Q are already available for some of the systems for which 57 Fe chemical shifts are known. In order to expand the body of available Mössbauer spectroscopic data to include the complexes having at least one trimethylphosphine ligand, , we have prepared a series of 94.5%-enriched 57 Fe(II) complexes of tetramesitylporphyrin (TMP) and octaethylporphyrin (OEP) having various bis- or mixed axial ligation, have used them for NMR studies, , and have now investigated them by Mössbauer spectroscopy.…”
Section: Introductionmentioning
confidence: 53%
“…1 It has been shown that microwave spectroscopy 2 could be used to probe the structure of this type of compound in the gas phase. Chloroferrocene has been studied with IR spectroscopy, 3 iron-57 and carbon-13 nuclear magnetic resonance ͑NMR͒ spectroscopy, 4 Mossbaüer spectroscopy, 5 photoelectron spectroscopy, 6 and mass spectrometry. 7 Presently, the microwave work provides the only insight into structural details of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[43] It has been postulated that high QS values (greater than that of ferrocene itself) in a-ferrocenylcarbenium systems are due mainly to the interactions between the empty p orbital on C exo with several occupied metal orbitals, probably most efficiently with one lobe of the d x 2 Ày 2, the central belt of d z 2, or one lobe of d zx . Such an interaction would disrupt the normal binding of the ferrocene system, [44] giving rise to a ring tilt angle on the ferrocene moiety and causing the d z 2 to take part in the bonding. [45] As a consequence, this would promote bending towards the iron centre.…”
mentioning
confidence: 99%